Proficiency indicators for Philippine STEAM (Science, Technology, Engineering, Agri/fisheries, Mathematics) educators - Morales, Marie Paz E. (Philippine Journal of Science, 2019)
The study aimed to develop a self-rating tool to determine the proficiency of Philippine Higher Education (PHE) STEAM (Science, Technology, Engineering, Agri-Fisheries, Mathematics) Educators. This design and development research emphasized elaborations of the Philippine Professional Standards for Teachers (PPST) in the tertiary STEAM education aligned with the Policies, Standards, and Guidelines (PSGs) of 46 STEAM programs (science – 22, technology – 7, engineering – 10, agriculture – 5, and mathematics – 2). The crafted indicators went through expert and statistical validations and analyses to establish the indicators’ content validity, construct validity, and reliability. The experts assessed the indicators’ similarity and variance, appropriateness, phraseology, and ambiguity of items and found that most items from the first version (90 items) suit the criteria and the country’s context. Principal axis factor (PAF) analysis showed that only 60 items represent the seven factor loadings generated from the analysis. These seven factors matched the seven TPCK dimensions: Factor 1 (TPACK [Technological Pedagogical Content Knowledge]), Factor 2 (TPK [Technological Pedogogical Knowledge]), Factor 3 (TCK [Technological Content Knowledge]), Factor 4 (PCK [Pedagogical Content Knowledge]), Factor 5 (TK [Technological Knowledge]), Factor 6 (PK [Pedagogical Knowledge]), and Factor 7 (CK [Content Knowledge]). The first four factors with a majority of the generated 60 indicators already explained more than half of the variance as per PAF. Furthermore, all seven factors and the entire set of 60 indicators obtained above standard reliability indices as per Cronbach’s alpha analysis, thus incurring valid and reliable 60 indicators of proficiency for PHE STEAM educators that may be utilized for reflective practice and policy inputs to Philippine STEAM Education.